The burden of seasonal influenza-associated complications in Italy: a systematic review. (20th October 2021) - Giacchetta, I; Primieri, C; Cavalieri, R; Domnich, A; de Waure, C
Abstract: Background: Influenza is the infectious disease with the highest impact on population health in the European Union in terms of disability-adjusted life years. Reliable country-specific influenza-associated burden estimates play a crucial role in informing prevention and control measures to minimize the health and economic burden of the disease. Our purpose was to provide a comprehensive summary of available scientific literature on the burden of seasonal influenza on the Italian population. Methods: We performed a systematic literature review of articles published until 31 July 2020. PubMed, Embase and Web of Science were searched. The search strategy included a combination of search terms related to burden, influenza and Italian population. We included studies investigating seasonal influenza-related complications and/or mortality in Italy. A meta-analysis of data was not pre-planned because of the expected heterogeneity in study populations and outcomes. Results: A total of 16 studies were included in the qualitative synthesis, out of an original yield of 9, 268 articles. Ten (62.5%) and 8 (50%) studies analyzed influenza-related complications and hospitalizations, respectively, while 8 (50%) assessed influenza-related deaths. Only 3 studies (19.7%) concerned pediatric age. The synthesis of results showed that patients with chronic conditions might have an increased risk for complications up to almost 3 times as compared to healthy people. Hospitalization due to influenza can occur from less than 1% to more than 5% according to the study setting (general practice or emergency room). Excess deaths rates were estimated to be over 6-fold higher for the elderly than for the rest of population. Conclusions: Although there are still gaps in existing data, there is evidence of the significant burden that influenza places each year especially on high-risk groups. Summaries of the available data may inform decision-making in regard to vaccine strategies and public health policies. Key messages: Existing data show evidence of significant burden of influenza on Italian population, especially on high-risk groups. Summaries of country-specific influenza-related burden are crucial in informing vaccine strategies.